THE EFFECTIVENESS OF JIWA JAGAD JAWI FROM AN EXPERIENTIAL MARKETING PERSPECTIVE (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
This paper investigates the experiential marketing efficacy of the Jiwa Jagad Jawi video, scrutinizing its impact on viewers through emotional engagement, cultural immersion, storytelling, and authenticity. Employing a qualitative approach, it analyses viewer comments sourced primarily from YouTube, alongside literature and case studies. The video is lauded for its ability to immerse audiences in a sensory-rich journey, evoking profound emotions, triggering memories, and fostering cultural connections. Through captivating visuals and authentic storytelling, it transcends traditional advertising methods, leaving a lasting impression and forging deep-seated connections with the audience. The findings underscore the transformative potential of experiential marketing strategies, providing valuable insights for future brand campaigns seeking to engage and resonate with audiences on a meaningful level.
Keywords: Experiential Marketing; Emotional Engagement; Cultural Immersion; Storytelling; Authenticity